Reducing isolation for educators through ECHO virtual communities of practice - Dickson, Elizabeth; Lardier, David T.; Verdezoto, Carolina S.; Hackett, Janna M. (Frontiers in Education, 2024)
Students in U.S. rural schools experience lower educational outcomes than their urban peers related to social determinants of health such as under resourced schools, shortages of qualified teachers and staff, and high poverty levels. Geographic, social, or professional isolation in rural communities can compound these disparities by contributing to high turnover of educators and staff. Virtual communities of practice (VCoPs) can address the needs of individuals in remote and rural communities. However, it is critical to understand if VCoPs meet rural school staff needs to support their students. Wenger’s Community of Practice (CoP) framework and the Project ECHO model for VCoPs guided this descriptive, qualitative arm of our study to explore experiences of school staff participating in VCoPs through Project ECHO. Thirteen ECHO for Education participants joined virtual focus groups to discuss their experiences and perspectives of VCoPs. Interview transcripts were inductively coded using the CoP framework with enhanced rigor through audit trails and member checking. Four predominant themes emerged from the interviews: 1) belonging/connected with others; 2) reduced sense of isolation; 3) exchange of new ideas/knowledge; and 4) sense of collaboration. Participants described how the VCoP they participated in resulted in positive professional and personal experiences including the support offered in context of working in rural schools during the COVID 19 pandemic. VCoPs can establish supportive professional networks for rural school staff working with students in under-resourced settings. Our theoretically-grounded results substantiate VCoP development as a systems-level approach to facilitate professional collaboration, mitigate staff turnover, diminish professional isolation, and support students in rural communities.